2023
DOI: 10.1021/acs.cgd.3c00126
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Unified Understanding of W2C Polymorphic Structures by First-Principles Calculations

Abstract: Tungsten subcarbide (W2C) is widely applied to industrial catalysts, military industries, and aerospace facilities because it possesses excellent high-temperature performance and superior mechanical properties. However, contradictory data on the crystal structure of W2C including its disordered and different ordered phases have been often reported in the literature, and atomic-scale understanding of W2C polymorphic structures has not yet reached a consensus. Based on the L′3-type lattice, we have performed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, CaCO 3 polymorphs can be selected and using different amorphous CaCO 3 precursors results in different crystalline polymorphs being formed . In addition, vacancy distribution in WC precursors results in different W 2 C polymorphs, indicating that the disorder in the precursors may affect the structure of the product.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, CaCO 3 polymorphs can be selected and using different amorphous CaCO 3 precursors results in different crystalline polymorphs being formed . In addition, vacancy distribution in WC precursors results in different W 2 C polymorphs, indicating that the disorder in the precursors may affect the structure of the product.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For the intermediate carbon dose (WC2–WC4), the GIXRD (1.5°) patterns clearly demonstrated the formation of β-W 2 C, with peaks located at 34.6, 38, and 39.5° and indexed to the (100), (002), and (101) planes, respectively (Figures S12–S15). , Remarkably, under the fast carburization conditions of carbon ion implantation, β-W 2 C was synthesized in WC1–WC4, which previously has proven difficult to achieve. , However, a transition from W 2 C toward WC occurred at the highest carbon fluence (2.5 × 10 17 at. cm –2 , WC5), with new peaks at 36.5, 42.4, and 32.5° assigned to γ-WC(111), γ-WC(200), and δ-WC(001), respectively. ,,,, Clearly, at such high carbon concentrations, the formation energy for WC was significantly lowered, and a transition toward the thermodynamically favored WC was observed.…”
Section: Resultsmentioning
confidence: 99%
“… , Remarkably, under the fast carburization conditions of carbon ion implantation, β-W 2 C was synthesized in WC1–WC4, which previously has proven difficult to achieve. , However, a transition from W 2 C toward WC occurred at the highest carbon fluence (2.5 × 10 17 at. cm –2 , WC5), with new peaks at 36.5, 42.4, and 32.5° assigned to γ-WC(111), γ-WC(200), and δ-WC(001), respectively. ,,,, Clearly, at such high carbon concentrations, the formation energy for WC was significantly lowered, and a transition toward the thermodynamically favored WC was observed. Previous DFT calculations have shown that the FCC γ-WC phase predominantly forms smaller nanoparticles, compared to its hexagonal counterpart (δ-WC). , This suggested that the WC5 film contained WC nanoparticles with a range of sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting SACs, characterized by their nonsaturated surface, single-atom configuration, and varying W and/or C compositions, demonstrate distinctive responses under different reaction environments. This makes them suitable models for investigating the structural evolution of catalysts and their reaction mechanisms. Previous studies have underscored the enhanced activity and stability of tungsten carbide-supported catalysts in oxygen reduction reaction (ORR) applications. , Notably, W 2 C, with its differing interstitial carbon atom count compared to that of WC, alters the symmetry of surface sites and atomic coordination, offering broader possibilities for structural modification. , Therefore, W 2 C-supported SACs are of significant interest, especially in catalyzing the ORR, for fundamental research into catalyst structural evolution and understanding the structure–activity relationship through systematic exploration. Our research is thus directed toward an in-depth investigation of the formation of the W 2 C substrate, the mechanisms of single-atom anchorage, the adaptability of the active phase under ORR conditions, and, ultimately, deciphering the fundamental principles governing the catalytic mechanism.…”
mentioning
confidence: 99%